VersKiK qualitative study design: actual follow-up needs of paediatric cancer survivors, their informal caregivers and follow-up stakeholder perceptions in Germany - Aleshchenko, Ekaterina; Swart, Enno; Voigt, Mathias; Langer, Thorsten; Calaminus, Gabriele; Glogner, Juliane; Baust, Katja (BMJ open, 2024)
IntroductionThis article presents the study design of the qualitative part of the VersKiK study (Long-term care, care needs and wellbeing of individuals after cancer in childhood or adolescence: study protocol of a large scale multi-methods non-interventional study) aiming to explore actual follow-up needs of childhood and adolescence cancer survivors and their informal caregivers, gaps in current follow-up care provision and trajectories of cancer survivors’ transition from paediatric to adult healthcare.Methods and analysisWe will conduct up to 30 interviews with survivors of childhood and adolescence cancer and their informal caregivers with up to 20 participant observations of follow-up appointments. The results of these will be discussed in up to four focus groups with healthcare professionals and representatives of self-help groups. The study design aims to evaluate follow-up care after childhood cancer considering perspectives from survivors, their informal caregivers as well as healthcare providers. The combination of different data sources will allow us to get an in-depth understanding of the current state of follow-up care after paediatric cancer in Germany and to suggest recommendations for care improvement.Ethics and disseminationThe VersKiK study was approved by the Ethics Committee Otto von Guericke University on 2 July 2021 (103/21), by the Ethics Committee of Johannes Gutenberg University Mainz on 16 June 2021 (2021-16035), by the Ethics Committee University of Lübeck on 10 November 2021 (21-451), by the Ethics Committee University of Hospital Bonn on 28 February 2022 (05/22). For each part of the qualitative study, a separate written informed consent is prepared and approved accordingly by the ethics committees named above.Trial registration numberRegistered at German Clinical Trial Register, ID: DRKS00026092.